2013
DOI: 10.1038/srep02821
|View full text |Cite
|
Sign up to set email alerts
|

The Non-innocent Phenalenyl Unit: An Electronic Nest to Modulate the Catalytic Activity in Hydroamination Reaction

Abstract: The phenalenyl unit has played intriguing role in different fields of research spanning from chemistry, material chemistry to device physics acting as key electronic reservoir which has not only led to the best organic single component conductor but also created the spin memory device of next generation. Now we show the non-innocent behaviour of phenalenyl unit in modulating the catalytic behaviour in a homogeneous organic transformation. The present study establishes that the cationic state of phenalenyl unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…Although a linear correlation between the concentration of the catalyst and the initial rate data often exists when rate is plotted against concentration, numerous studies have shown that the regression line does not intersect with the origin (eq 1, A ≠ 0; also see Figure 1). If there is no background reaction, the rate should be 0 when the catalyst concentration is 0, so A (intercept) should also be 0, but this is not the case in many reactions ( A is usually less than 0), 1 indicating that a threshold catalyst concentration is required. Beyond vaguely implying some sort of catalyst poisoning, literature reports have not addressed the causes of this type of threshold.…”
mentioning
confidence: 99%
“…Although a linear correlation between the concentration of the catalyst and the initial rate data often exists when rate is plotted against concentration, numerous studies have shown that the regression line does not intersect with the origin (eq 1, A ≠ 0; also see Figure 1). If there is no background reaction, the rate should be 0 when the catalyst concentration is 0, so A (intercept) should also be 0, but this is not the case in many reactions ( A is usually less than 0), 1 indicating that a threshold catalyst concentration is required. Beyond vaguely implying some sort of catalyst poisoning, literature reports have not addressed the causes of this type of threshold.…”
mentioning
confidence: 99%
“…For the second condition, we mixed propargyl amide 3-1 with catalytic amounts of Ph3PAu + OTf -and a strong acid, TfOH; the purpose of the strong acid was to make sure that the all the vinyl gold complex was protonated (Figure 14c). When monitored by 31 P NMR, both conditions ended up generating a single new peak at around 45 ppm (Figure 14b and Figure 14c). Hashmi and co-workers proposed that in the hydration of alkynes, a cluster of water molecules might act as proton shuttle to facilitate the protodeauration of a protonated vinyl gold intermediate.…”
Section: A4-a8mentioning
confidence: 99%
“…Although a linear correlation between the concentration of the catalyst and the initial rate data often exists when rate is plotted against concentration, numerous studies have shown that the regression line does not intersect with the origin (eq 1, A≠0; also, see Figure 19). If there is no background reaction, the rate should be zero when the catalyst concentration is zero, so A (intercept) should be zero, but this is not the case in many reactions (A is usually less than zero), [30][31][32] indicating that a threshold catalyst concentration is required. Beyond implying some sort of catalyst poisoning, literature reports have not addressed the causes of this type of threshold.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations